Nanoscale to Macroscale Characterization of in—Situ Bacterial Biopolymers for Applications in Soil Stabilization - Ramachandran, Asha Latha; Mukherjee, Abhijit; Dhami, Navdeep K (Frontiers in Materials, 2022)
Bacterial biopolymers produced extracellularly due to microbial metabolic activities have gained considerable interest in various engineering applications. The major advantages of bacterial biopolymers is their in-situ production and low water solubility, eliminating the requirement for mixing in granular substrates such as soils. These properties make them highly desirable and preferable than manufactured biopolymers. But for any engineering applications, it is crucial to understand the mechanical properties of these materials which have been less explored. This investigation is the first attempt to quantify the nano and macro mechanical properties of in-situ bacterial biopolymer dextran produced by bacterial culture Leucononstoc mesenteroids. The fundamental mechanism of bacterial biopolymer-based cementation has been revealed through their morphographic and nanomechanical testing via atomic force microscopy, nanoindentation and scanning electron micrographs. Effect of bacterially produced biopolymers and commercial biopolymers on macro-mechanical properties of soils was then investigated via needle penetration tests. In-situ biopolymers were found to be highly effective in stabilizing soils with comparable mechanical properties as commercial biopolymers. This study has demonstrated novel methods for testing in situ polymers and opened up the channels for their applications in numerous subsurface as well as surface applications.